Pelvic inflammatory disease presenting 16 months after vaginal hysterectomy: A case report and literature review - Eloy Cabello-Garcia; Elena Ferriols-Pérez; Berta Urpí-Tosar; Mireia González-Comadran (Elsevier, 2021)
Pelvic inflammatory disease after hysterectomy is rare and the underlying route of infection is highly heterogeneous. We report the case of a 52-year-old woman with a history of vaginal hysterectomy for uterine prolapse admitted to the emergency department with acute abdominal pain and fever. Vaginal discharge and pelvic tenderness were evident in the clinical examination. Ultrasound and computed tomography scans showed a cystic pelvic mass in contact with the vaginal cuff, suggesting the diagnosis of pelvic inflammatory disease. Laparoscopic examination revealed a bilateral tubo-ovarian abscess firmly attached and fistulized to the vaginal cuff, and after tubal removal and antibiotic coverage the patient had an optimal recovery. We performed a review of the case reports published on this subject, and concluded that pelvic inflammatory disease should not be excluded in patients with a history of hysterectomy when symptoms and findings are compatible.